ANTIMICROBIAL RESISTANCE AND MORTALITY: lessons from the ICU - Hariyanto, Hori; Yahya, Corry Quando; Cucunawangsih, Cucunawangsih; Pertiwi, Cecilia Lenny Pravita (African Journal of Infectious Diseases (AJID), 2022)
Background: Antibiotic resistance has been a long-debated topic since decades ago. The development of stronger, newer antibiotics, implementation of antibiotic stewardship and revised guidelines remain the main focus of our society to prevent resistancy. But is it really resistancy that cause higher mortality to patients with multidrug resistance (MDR) infections? Methods: We conducted a cohort retrospective study from 2016 to 2019 in our Intensive care unit (ICU). Antimicrobial susceptibility test (AST) results were analyzed for their association with patient mortality outcomes. Results: Over the four-year period, 381 positive bacterial cultures were analyzed and 51% of them grew MDR pathogens upon their first culture. The overall mortality rate was 19% (38/195), and there was no significant association between MDR and mortality; p 0.387. A strong association was however found between patients with medical cases with an OR 1.76; CI 1.76-2.55; p 0.003 and those with APACHE scores ≥20 upon admittance to the ICU, OR 1.32; CI 1.68-8.29; p 0.001. Conclusion: Resistancy is not the true cause of mortality. Infection by resistant microbes does not necessarily mean the worst outcome since virulency is the actual cause of pathogenicity, and thus mortality.